Pattern of Hormone Receptors (Estrogen and Progesterone) and Human Epidermal Growth Factor 2 Status in Breast Cancer Patients in a Tertiary Care Centre - Ray, Suchanda; Chowdhury, Shajia; Hossain, Md Abed; Alam, Md Ishtiaque (Jalalabad Medical Journal, 2026)
Breast cancer remains one of the most prevalent malignancies affecting women globally, with significant morbidity and mortality rates. Hormone receptor status, particularly estrogen receptor (ER) and progesterone receptor (PR), along with human epidermal growth factor receptor 2 (HER2) statuses, are pivotal factors influencing breast cancer progression and therapeutic responses. This study aims to analyse the estrogen and progesterone receptor and HER2 status in breast cancer patients treated at a tertiary care centre. This cross-sectional study was conducted from June 1, 2023, to November 30, 2023, at Jalalabad Ragib-Rabeya Medical College Hospital, Sylhet. Data were collected from medical records, pathology reports, and treatment records of 81 female breast cancer patients. ER positive status was found in 60.5% of patients, and PR positive status in 49.4%. HER2 positivity was present in 19.8% of patients. Invasive ductal carcinoma was the most common histopathological subtype (86.4%), with grade II tumours being the most prevalent (81.5%). ER and PR positivity was found in 62.8% and 51.4% of cases of invasive ductal cell carcinoma, while HER2 was found in 22.8% of cases. This study highlights the demographic and molecular characteristics of breast cancer patients in a tertiary care centre, emphasising age-related variations in hormone receptor and HER2 status. The findings underscore the importance of comprehensive profiling in optimising breast cancer management and support the need for further research to enhance treatment strategies and improve patient outcomes. Jalalabad Med J 2025; 22 (1): 28-32